Human trafficking and slavery reconsidered: conceptual limits and states' positive obligations in European law - Stoyanova, Vladislava (Cambridge University Press, 2017)
"By reconsidering the definitions of human trafficking, slavery, servitude and forced labour, Vladislava Stoyanova demonstrates how, in embracing the human trafficking framework, the international community has side-lined the human rights law commitments against slavery, servitude and forced labour that in many respects provide better protection for abused migrants. Stoyanova proposes two corrective steps to this development: placing a renewed emphasis on determining the definitional scope of slavery, servitude or forced labour, and gaining a clearer understanding of states' positive human rights obligations. This book compares anti-trafficking and human rights frameworks side-by-side and focuses its analysis on the Council of Europe's Trafficking Convention and Article 4 of the ECHR. With innovative arguments and pertinent case studies, this book is an important contribution to this field and will appeal to students, scholars and legal practitioners interested in human rights law, migration law, criminal law and EU law"--